Beliefs about immunosuppressant medication and correlates in a German kidney transplant population - Bünemann, Maybrit; Bauer-Hohmann, Maximilian; Klewitz, Felix; Kyaw Tha Tun, Eva Marie; Tegtbur, Uwe; Pape, Lars; Schiffer, Lena; Schiffer, Mario; de Zwaan, Martina; Nöhre, Mariel (Journal of psychosomatic research, 2020)
Objective: A common reason for organ rejection after transplantation is the lack of adherence regarding immunosuppressive medication (ISM). A variety of different aspects can promote non-adherent behavior, including the relationship between perceived benefits and concerns regarding ISM (“necessity-concerns-framework”). Little is known about the variables associated with this framework. Methods: As part of this cross-sectional study, 570 patients after kidney transplantation who participated in a structured multimodal follow-up program (KTx360°) were examined in two transplant centers in Lower Saxony. We used the Beliefs about Medicines Questionnaire (BMQ) to evaluate the patients' believes and concerns regarding their ISM. Results: The mean age of the participants was 51.9 (SD 14.17) years, 58.4% were men, and 25.8% had ≥12 years of school attendance. The mean time since transplantation was 65.9 months. In patients undergoing kidney transplantation, the perceived benefit of ISM mostly exceeded the concerns. We found an association between lower perceived benefits and greater concerns and lower adherence. Also, a higher perceived necessity was significantly associated with higher age and lower levels of depression and anxiety. Greater concerns were significantly associated with more symptoms of depression and anxiety, lower perceived social support, and lower kidney functioning (eGFR). Conclusion: Even though patients after kidney transplantation usually acknowledge the importance of their ISM, they still have considerable concerns that are associated with less adherence and various psychosocial risk factors. Further longitudinal studies are needed to assess the extent to which beliefs about medication are variable and can be individually addressed to improve adherence.
CRIS-Team Scopus Importer:2020-03-17
Keywords: Adherence; Beliefs about medicines; Immunosuppressive medication; Kidney transplantation; Renal transplantation